2020
DOI: 10.1186/s12889-020-8212-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in quality of life among community-dwelling older adults in low- and middle-income countries: results from the Study on global AGEing and adult health (SAGE)

Abstract: Background: Quality of life (QoL) is an important component of individuals' general well-being, particularly in older adults. However, factors influencing QoL among older adults in low-and middle-income countries (LMICs) have not been fully examined. Furthermore, the role of gender differences in relation to QoL in multiple LMICs has also not been examined in detail. Methods: This study used data from the World Health Organization's Study on global AGEing and adult health (SAGE), Wave-1. Based on a literature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 28 publications
11
51
4
6
Order By: Relevance
“…Corroborating this, a meta-analysis of 146 studies showed negligible effects of gender on well-being, where it only accounted for less than 1% of the well-being scores [ 58 ], which also paralleled the findings of a cross-country study [ 58 ]. The lack of statistical significance could be a consequence of the increasing awareness of gender equality, which provides equal roles and opportunities to both males and females in the decision making process [ 64 ]. However, this negated the results of other studies that concluded a better QOL among men than females in rural areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroborating this, a meta-analysis of 146 studies showed negligible effects of gender on well-being, where it only accounted for less than 1% of the well-being scores [ 58 ], which also paralleled the findings of a cross-country study [ 58 ]. The lack of statistical significance could be a consequence of the increasing awareness of gender equality, which provides equal roles and opportunities to both males and females in the decision making process [ 64 ]. However, this negated the results of other studies that concluded a better QOL among men than females in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome from this study also showed a better perceived QOL across all domains among younger residents (age 18 to 59 years) than the elderly (60 years and above), which was consistent with the results of previous works [ 41 , 50 , 65 ]. The deteriorating health conditions, including mental health, limited mobility and age-related prejudice, most likely explains the poor psychological, physical, social and environmental domains of QOL among the elderly population [ 41 , 64 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Previous studies have assessed the psychometric properties and reported good internal consistencies (0.72–0.85) and acceptable convergent validity (0.61–0.77) with WHO QOL BREF. [ 13 14 15 ]…”
Section: Methodsmentioning
confidence: 99%
“…Women are generally more symptomatic than men when they present with HFrEF (100), which could in turn be related to a later medical contact, minimization of symptoms, acceptance of a poorer quality of life (101) and a prioritization of their social role as caregivers. Due to underrepresentation in clinical trials, we have limited information on the efficacy and adverse effects of therapies in women.…”
Section: Discusionmentioning
confidence: 99%